Surgical Expertise in Neonatal Extracorporeal Membrane Oxygenation (ECMO): A Single Center Experience - Macchini, Francesco; Di Cesare, Antonio; Morandi, Anna; Ichino, Martina; Raffaeli, Genny; Conigliaro, Federica; Sorrentino, Gabriele; Neri, Simona; Mosca, Fabio; Leva, Ernesto; Cavallaro, Giacomo (Frontiers in Pediatrics, 2019)
Introduction: The surgical technique for peripheral cannulation aimed to provide extracorporeal membrane oxygenation (ECMO) is well described. Training methods for surgeons still need a proper standardization, especially in newborn patients. This study aims to evaluate the outcomes of surgical training of a neonatal ECMO team. Materials and Methods: A five years training program (2014-2018) was developed to achieve the skills in the surgical technique for neonatal veno-arterial ECMO. Surgeons with experience in neonatal and vascular surgery were selected for the training. The training consisted of educational sessions, high-fidelity simulations, swine model in vivo procedures, international fellowship, and periodical simulations. The preliminary clinical experience in surgical neonatal ECMO management (2016-present) was analyzed recording the following data: indications for ECMO and patients’ data; effectiveness of cannulations (number; perioperative complications of cannulation; major surgical events during ECMO); efficacy of de-cannulation (number and perioperative complications). Results: 12 neonates (5 females) fitted the ELSO criteria for ECMO. Nine newborns were affected by CDH; 1 by H1N1 flu-related pneumonia; 1 by meconium aspiration syndrome and one by Respiratory Syncytial Virus related bronchiolitis. Mean weight at cannulation was 3.281 g (range 2.330-3.840 g); mean gestational age was 36 weeks. No procedure was aborted, and no intra-operatory mortality was recorded. Mean operative time was 86±30 minutes. The carotideal cannula caliber ranged from 8F (8 patients) to 10F (2 patients); the jugular cannula caliber were: 8F cannula (2 patients), 10F (6 patients) and 12F (2 patients). Four complications occurred: a case of air in the circuit, two cases of azygous vein cannulation and a partial dislocation of the venous cannula during the daily care maneuvers. All of them were promptly recognized and successfully treated. The mean ECMO duration was 7.1 ± 4.2 days (range 2-16 days). Seven patients (78%) were decannulated effectively. Mean decannulation time was 53 minutes (range 45-80 minutes). No complications occurred during the decannulation process. No ECMO–related deaths were recorded. Conclusions: Neonatal respiratory ECMO still represents a challenge. Experienced neonatal surgeons can manage the neck vascular cannulation. Adhesion to the codified procedure after an appropriate training and learning curve is mandatory.